Improving the strength performance and economic viability of Eucalyptus Camaldulensis through finger jointing - Amal, Hany (AUC Knowledge Fountain, 2020)
Egypt is known with its arid weather and the presence of a very limited space of greenery mainly around the Nile River and mostly for agriculture uses. Therefore Egypt has always lacked the presence of forestry due to the scarcity of water supply which has led to a historical low production of local wood. Therefore, Egypt sustains the domestic needs of wood through imports from several regions of the world; mainly, Europe, North American, and Asia .Nevertheless, Egypt has abundance of homegrown trees that grow with low water consumption often irrigated through the use of waste water that are grown informally . Eucalyptus Camaldulensis is one of the widely grown trees in Egypt and are present in huge numbers; however they are not vastly used in the Egyptian market for construction applications as a competitor to the imported wood types; however they are mainly being used as wood fuel. In fact, as previous studies show Eucalyptus Camaldulensis has high mechanical properties and relatively cheap prices that allow it to compete with imported wood types like pine or oak. However due to the informality and the limited studies on the wood, it is not gaining the presence it can achieve in the construction market. The mechanical properties of eucalyptus Camalednis enable it to be used in vast uses as in outdoor and indoor applications in flooring, furniture and more. The main objective of this research is to develop finger joints that enhance the properties of the wood and solve the problem of abundance of defects in the wood and small production sizes. Finger joints can mitigate the problem by omitting the defected part and connecting the wood in a very strong way that can enable it to be used in vast uses Next step was to determine the standard test methods, procedures, required types of equipment’s and apparatus according to standards. To evaluate different finger joints, glue types, humidity cycle, and joints accuracy. These factors are then all tested so that the best configuration can be chosen to maximize the gains of finger joints, and enhance the quality of eucalyptus Camaldulensis wood. It was then concluded after analyzing tests results that finger length of 12mm had a significant effect on increasing the flexural strength of the wood. Moreover, the glue type of MUF had a superior quality when compared to polyvinyl acetate which had a significant effect in increasing the strength of the wood. The quality of the finger joint which indicates the level of accuracy in cutting the wood and jointing them with glue without having much space in between became very apparent in lifting the flexural strength of wood when the joints are done accurately. These preferable factors when combined together achieved an average flexural strength of 75.37 MPa in the 3 point bending test and 45.4 MPa in the 4 point test, achieving an average of 68% in the 3 point test and an average of 62.5% in the 4 point test of the original strength of solid wood with no finger joints that achieved an average of 111.1 MPa in the 3 point bending test and average of 72.62 MPa in the 4 point test,. Therefore, through proper manufacturing of finger joints it is possible to produce Eucalyptus Camaldulensis in bigger sizes and defects free pieces with a considerable percentage of its original strength to be used in vast number of construction applications. Therefore improving the economic viability and maximizing the added value on Eucalyptus Camaldulensis and raising its price from 1,200 LE a m3 of raw or 5,000 LE for processed short sized wood to 12,000 LE a m3 for finger jointed wood in large sizes and defects free quantities.